2020
DOI: 10.18203/2349-2902.isj20200830
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal onlay versus dorsal inlay buccal mucosal graft urethroplasty for anterior urethral stricture: a single centre retrospective study

Abstract: Background: Urethral stricture is a relatively common disease. The choice of surgery is based on the stricture location, length of the stricture and etiology. Buccal mucosal graft (BMG) urethroplasty with Asopa and Kulkarni techniques, revolutionized the approach to anterior urethral stricture repair. Objective of the study was to compare both the dorsal onlay BMG urethroplasty technique of Kulkarni and the dorsal inlay BMG urethroplasty technique of Asopa for the management of long anterior urethral stricture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
1
1
1
Order By: Relevance
“…In the study of Vasudeva et al [21] who compared the dorsal onlay versus ventral onlay for treating bulbar urethral stricture by BMG, they reported 92.5% success rate when using dorsal onlay technique and 90% success rate when using ventral onlay procedure. In a metanalysis that was done by Bagchi et al [22] , who compared between the different types of grafts that used in urethral reconstructions after stricture, they found that the success rate when using BMG is 85.9%, which is in line with our study findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the study of Vasudeva et al [21] who compared the dorsal onlay versus ventral onlay for treating bulbar urethral stricture by BMG, they reported 92.5% success rate when using dorsal onlay technique and 90% success rate when using ventral onlay procedure. In a metanalysis that was done by Bagchi et al [22] , who compared between the different types of grafts that used in urethral reconstructions after stricture, they found that the success rate when using BMG is 85.9%, which is in line with our study findings.…”
Section: Discussionsupporting
confidence: 92%
“…The type of the operative procedure was significantly affected the success rate (P value < 0.003) as it was high in dorsal onlay (97.1%) more than ventral onlay (66.6%), which disagrees with the result of Bagchi et al [22] , who found no significant difference between the two procedures as regarding the success rate. Volume of blood loss significantly affects the success rate (P value = 0.001) as the percentage of succeed patients in those who lost < 500 ml blood was 87.3%% and in those who lost > 500 ml was 0%.…”
Section: Discussioncontrasting
confidence: 60%
“…However the results obtained from the dorsal onlay urethroplasty aided with the buccal mucosal graph and vaginal wall graph were compared. These treatment are proved to be more effective with better results and less reported complications [9][10] .…”
Section: Introductionmentioning
confidence: 99%